Variation in leaf wax n-alkane characteristics with climate in the broad-leaved paperbark (Melaleuca quinquenervia). (April 2019) - Andrae, Jake W.; McInerney, Francesca A.; Tibby, John; Henderson, Andrew C.G.; Hall, P. Anthony; Marshall, Jonathan C.; McGregor, Glenn B.; Barr, Cameron; Greenway, Margaret
Highlights: n -Alkanes were characterised across both temporal and spatial variations in climate. Characteristics show little correlation with climate through time at a site. Characteristics correlate significantly with climate across a large spatial transect. Correlations are consistent with the functional role of n -alkanes. Sub-fossil leaf wax records are likely to reflect large climatological shifts. Abstract: In higher plants, leaf waxes provide a barrier to non-stomatal water loss, and their composition varies both between and within species. Characteristics of n -alkanes, a suite of ubiquitous compounds in these waxes, are thought to be influenced by the availability of water and the temperature in a plant's growing environment. Longer n -alkane distributions with less variability in chain length are hypothesised to confer greater resistance to non-stomatal water loss and thus are expected in higher abundance in desiccating environments. Relationships between the distribution of n -alkanes and both precipitation and temperature have previously been observed. Despite this, it is unclear whether n -alkane chain length distributions vary plastically in response to climate, or whether they are fixed within populations in different climate settings. To better understand this, we examine the relationship between n -alkane characteristics of Melaleuca quinquenervia and both spatial and temporal climate variation. Across eastern Australia, we find that n -alkane homolog concentrations and distributions in leaves of M. quinquenervia do not vary with climate where samples are proximate, even when climate shows significant variability. However, the concentration and distribution of n -alkane homologs do differ considerably between geographically separated populations in very different climate regimes. These results suggest n -alkane characteristics are not a plastic response to climate variability, and instead are likely fixed and could be driven by genetic differences between populations. This has important implications for the use of n -alkane characteristics as palaeoenvironmental proxies.